Simple rules and the emergence of complexity in surface chirality. Issue 98 (3rd October 2016) - Forster, M.; Raval, R.
Abstract : Surface chirality arising from self-organized molecular monolayers may manifest both a handedness and footedness, leading to a dual level of chiral expression. Abstract : Surface chirality arising from self-organized molecular monolayers may manifest both a handedness and footedness, leading to a dual level of chiral expression. Recent advances have determined both levels of chirality at the single-molecule level and, surprisingly, reveal a plethora of chiral orderings. There is yet no clear understanding of why such varied manifestations of interface chirality occur. Here, we show that the ordering of handedness and footedness of amino-acids within ( n × 2) assemblies on Cu(110) may be understood on the basis of three simple generic rules from which a variety chiral expressions naturally arise. These rules also provide insights into how enantiomer assembly at surfaces may be tailored to produce required chiral organizations and segregations.